Global trade of medicinal and aromatic plants. A review - Sahar Zamani; Mehran Fathi; Mohammad-Taghi Ebadi; Ákos Máthé (Journal of Agriculture and Food Research)
Medicinal and aromatic plants (MAPs) are essential natural resources with applications in pharmaceuticals, food, cosmetics, and pesticides. With growing consumer preferences for natural products, the global trade of MAPs (HS code: 1211) has grown significantly. This study analyzed global MAP market trends using export and import data from the International Trade Center (ITC) from 2010 to 2023. During this period, global export and import values surged by 97.8 % and 98.1 %, reaching $4.18 billion and $4.25 billion, respectively, in 2023. China and India emerged as key exporters, with India achieving a 240 % growth in export value, while the United States, Germany, and Japan were leading importers due to high domestic demand and advanced processing infrastructure. HS 121190, comprising plants for perfumery, pharmacy, and pest control, accounted for over 90 % of total trade value, ranking as the 976th most traded product globally in 2022. MAPs prices vary by origin, with vanilla ($115–255.39/kg) as the most expensive and arugula ($0.12/kg) the cheapest. Certifications like WHO-GACP and GMP are critical for quality assurance, traceability, and market competitiveness. Challenges include overharvesting, habitat destruction, trade barriers, and inconsistent quality control, necessitating sustainable cultivation, advanced processing technologies, and harmonized regulations. While Asia-Pacific, led by China and India, dominates production due to biodiversity and supportive policies, Europe and North America focus on value-added re-export. This study underscores the pivotal role of MAPs in global trade. It also provides actionable insights for stakeholders to optimize strategies, embrace sustainability, and capitalize on the expanding demand for these versatile plants.